Numerical Simulation of Flow in a Solar Chimney Power Plant - Sommanawat, Wichain (International Journal of Integrated Education and Development, 2018)
In this study, a Finite Element Method (FEM) based program for steady-state viscous incompressible thermal flows is developed and utilized to simulate laminar flow in a Solar Chimney Power Plant (SCPP). The flow characteristics in the SCPP system is studied by comparing the distribution of velocity, temperature and pressure from three different types of connection between a solar collector and a chimney. It is found that the curved junction with a diffuser is the most suitable model for adopting the SCPP in practice.